The Smugglers : an investigation into the world of the contemporary smuggler. - Green, Timothy (London : Michael, Joseph, 1969)
A smugglers works from inclination, from passion. He is on one side an artist. He risks everything, run terrible dangers; he is cunning, invents dodges, and gets out a scrapes, and sometimes acts with a sort of inspiration. It is a passion as strong as gambling.
Including bibliographical index
osa 22/01/19
Loans
Keywords: Smuggling